A Review on Revolutionizing Pediatric Dental Treatments with 3D Printing Technology: Current Trends and Future Prospects - B, Greeshma (Journal of Orofacial Research, 2025)
The advent of 3D printing technology has revolutionized the field of dentistry, leading to significant advancements in clinical applications and research. The integration of 3D printing with CAD CAM technology facilitates the layer by layer manufacturing of three dimensional objects by sequentially adding material. 3D printing is a resourceful technique that allows the development of fully digitalized and personalized treatment plans, thereby helping to customize dental appliances for patients. It is highly competent, replicable, and provides fast and precise results in a reasonably priced style. Recently, 3D printing technology has played a major role in pediatric dentistry from the printing of individualized imprint trays, orthodontic models, maxillo facial growth evaluation, interceptive appliances, fabrication of prosthetics, and crowns, during fracture, surgical cases, and navigating complex root canal treatments in pediatric patients. Through this review, we intend to discuss the scope of 3D printing in the field of pediatric dentistry.